2003
DOI: 10.1071/ea02099
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen fertiliser on potato (Solanum tuberosum L., cv. Russet Burbank) in Tasmania. 1. Yield and quality

Abstract: Thirteen field trials were conducted on ferrosols and tenosols in Tasmania to assess the response of potatoes (Solanum tuberosum L., cv. Russet Burbank) to basal (up to 250 kg/ha) and topdressed (up to 100 kg/ha) nitrogen fertiliser. Economic yield responses to basal nitrogen were obtained at 9 sites. Topdressing did not increase yield compared with equivalent rates of basal nitrogen, and often failed to compensate for a lack of nitrogen applied at planting. This lack of response may reflect the inability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
3
5
0
1
Order By: Relevance
“…It could be inferred that N was provided later in 2011 cropping season by fall green manure decomposition which delayed potato maturity, resulting in lower tuber specific gravity [61]. Our results corroborate earlier studies in eastern Canada [55] and other investigations that reported that excess N decreases potato specific gravity, particularly during the tuber bulking growth stage [62].…”
Section: Tuber Specific Gravitysupporting
confidence: 90%
“…It could be inferred that N was provided later in 2011 cropping season by fall green manure decomposition which delayed potato maturity, resulting in lower tuber specific gravity [61]. Our results corroborate earlier studies in eastern Canada [55] and other investigations that reported that excess N decreases potato specific gravity, particularly during the tuber bulking growth stage [62].…”
Section: Tuber Specific Gravitysupporting
confidence: 90%
“…For the maximum marketable yield, N fertilization rates ranged between 151 and 250 kg ha −1 (Bélanger et al 2000a). Silva et al (2007) obtained the maximum tuber yield of 40.72 Mg ha −1 with 178 kg ha −1 of N. In nine of thirteen Tasmanian field studies, Sparrow and Chapman (2003) obtained potato yield responses to N applied at planting whereas split N applications did not improve tuber yield and quality.…”
Section: Total and Marketable Tuber Yieldmentioning
confidence: 98%
“…Com relação à coloração dos chips, os resultados reforçam observações anteriores feitas por SPARROW & CHAPMAN (2003), os quais concluíram que os efeitos do N sobre a coloração do chips são pequenos e de reduzida importância comercial. Isso significa que os efeitos do N ocorreriam de forma predominante no equilíbrio entre o crescimento da parte aérea e dos tubérculos, o qual determina a partição da matéria seca entre esses dois compartimentos da planta.…”
Section: O Objetivo Do Trabalho Foi Determinar O Teor De Matéria Secaunclassified